Advanced Study of Drought-Responsive Protein Pathways in Plants - Ali Movahedi; Raphael Dzinyela; Soheila Aghaei-Dargiri; Abdul Razak Alhassan; Liming Yang; Chen Xu (Agronomy, 2023)
Drought, the most significant environmental stressor, severely limits plant growth and development and significantly reduces crop production. Drought stress responses vary among plants, allowing them to withstand and survive adverse conditions. Plants resist drought by maintaining signaling pathways, such as the abscisic acid pathway, and activating unusual proteins, such as dehydrins. This study aims to investigate signaling pathways and the biological structures and activities of proteins involved in these processes. We also look into the occurrence of crosstalk across multiple signaling pathways and what it means for agricultural plant enhancement. By incorporating the most common components across all abiotic stress situations, this review provides insight into the evolution of drought stress tolerance in agricultural plants. This review could be helpful for crop drought stress researchers.